Pengaruh Komunikasi Interpersonal Guru terhadap Perilaku Belajar Siswa Beragama Buddha: The Influence of Teachers' Interpersonal Communication on the Learning Behavior of Buddhist Students - Tejo Ismoyo; Uswatun Khasanah; Taridi Taridi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Teacher interpersonal communication is an important component of learning that shapes teacher-student interactions. The quality of effective communication can influence students' learning behavior in attention, participation, discipline, and academic responsibility. Observations at Pelita Bangsa Elementary School found suboptimal student learning behavior, including low concentration, low participation, and poor discipline. This condition indicates the importance of examining the influence of teacher interpersonal communication on the learning behavior of Buddhist students. This study aims to analyze the levels of teacher interpersonal communication and Buddhist student learning behavior, and the influence of teacher interpersonal communication on student learning behavior at Pelita Bangsa Elementary School. This study used a quantitative, correlational design through field research. The sample consisted of 38 Buddhist students. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The reliability test showed a Cronbach's Alpha of 0.975 for teacher interpersonal communication and 0.981 for learning behavior. Data analysis used simple linear regression and product-moment correlation with SPSS. The results of the study showed t = 7.740 > t table = 1.688 (p < 0.05), a correlation coefficient (R) of 0.790, and a determination coefficient (R²) of 0.625. Teacher interpersonal communication accounted for 62.5% of student learning behavior, while other factors influenced 37.5%. In conclusion, teacher interpersonal communication has a positive and significant influence on the learning behavior of Buddhist students at Pelita Bangsa Elementary School. It is an important factor in optimizing learning.